1999
DOI: 10.1007/bf02565167
|View full text |Cite
|
Sign up to set email alerts
|

Subverting bacterial resistance using high dose, low solubility antibiotics in fibrin

Abstract: Antibiotics (ABs) delivered from fibrin were evaluated for control of multi-drug resistant (MDR) Staphylococcus aureus. ABs having low aqueous solubility (< or = 1 mg/ml) were encapsulated by fibrin (composed of fibrinogen, thrombin, Factor XIIIa and calcium chloride) and examined. Electron microscopy revealed fibrin-caged, tetracycline crystals that were 0.26 to 2.8 microns in size and bound within the reticular matrix. Antibiograms documented that S. aureus ATCC 27659 was resistant to erythromycin (ERY), pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The antibiotic streptomycin has low aqueous solubility, but when encapsulated by fibrin matrices had enhanced efficacy in preventing host lethality in a rat model of experimental multidrug-resistant S. aureus peritonitis. 70 However, the contribution of fibrinogen to host defense against S. aureus peritonitis goes beyond simple clumping or entrapment of bacteria.…”
Section: Fibrinogen As a Central Mediator Of Host Defense In S Aureumentioning
confidence: 99%
“…The antibiotic streptomycin has low aqueous solubility, but when encapsulated by fibrin matrices had enhanced efficacy in preventing host lethality in a rat model of experimental multidrug-resistant S. aureus peritonitis. 70 However, the contribution of fibrinogen to host defense against S. aureus peritonitis goes beyond simple clumping or entrapment of bacteria.…”
Section: Fibrinogen As a Central Mediator Of Host Defense In S Aureumentioning
confidence: 99%
“…When poorly soluble antibiotics are entrapped in a fibrin matrix at concentrations greater than their solubility, they are deposited as hetero geneously sized crystals and released into the medium gradually [42]. In a more recent study, it has been shown that the release of entrapped molecules is also hampered by their binding to the matrix proteins or those entrapped within the matrix during the formation of fibrin net works [5,43].…”
Section: Discussionmentioning
confidence: 99%
“…Many papers demonstrated that FG combined with antibiotics inhibits bacterial growth in vitro and in vivo (Harry et al ., 1991; Woolverton et al ., 1999). Here, we aimed to investigate the possible role of FG as the conditioned media for bacterial growth.…”
Section: Discussionmentioning
confidence: 99%